Determinan Lama Waktu Kesembuhan pada Pengobatan Pasien Tuberkulosis Kategori I - Azizah, Ita (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2020)
57% of Tuberculosis patients in Ungaran District Hospital recover within 9-12 months. The purpose of this study was to determine the length of time determinants of recovery in the treatment of tuberculosis patients. This study uses a case control design. The number of samples used was 56 which were taken using purposive sampling. The results showed that variables related to the duration of recovery in the treatment of Tuberculosis patients in category I are the level of education (p value = 0.043, OR = 16.500), income level (p value = 0.013, OR = 4.231), smoking habits (p value = 0.032 , OR = 3.263), nutritional status (p value = 0.011, OR = 0.222) and the presence of other diseases (p value = 0.016, OR = 3.864), while variables which are not related to the length of time of recovery are the patient's age (p value = 0.781 ), type of TB (p value = 0.310), regularity of treatment (p value = 0.217), and side effects of OAT (p value = 0.508). Suggestions given for future researchers are to conduct research with qualitative methods and examine other variables that might be influential such as the quality of health services. Keywords: Determinant, Healing Time, Tuberculosis category I